The Transcription Factor SOX18 Inhibitor Small Molecule 4 Is a Potential Treatment of Cancer‐Induced Lymphatic Metastasis and Lymphangiosarcoma - Katja K. Koll; Martin M. Zimmermann; Patrick A. Will; Ulrich Kneser; Christoph Hirche (Cancer Reports)
ABSTRACT Background Malignant tumors release growth factors, promoting lymphangiogenesis in primary tumors and draining sentinel lymph nodes, ultimately facilitating lymph node metastasis. As a malignant lymphatic tumor entity, lymphangiosarcomas are characterized by low survival rates and limited treatment options. The transcription factor SOX18 plays a crucial role in both lymphatic endothelial cell differentiation and cancer‐induced lymphangiogenesis. Aims In this in vitro study, we investigated the potential therapeutic effect of a small molecule called Sm4, which inhibits SOX18, on lymphatic endothelial and lymphangiosarcoma cells in vitro. Methods and Results Human dermal lymphatic endothelial cells (HDLECs), lymphangiosarcoma cells (MO‐LAS), and other endothelial cell lines were cultured. We found that Sox18 exhibited high mRNA expression levels in both HDLEC and MO‐LAS. Sm4 treatment decreased the Sox18 expression level at the mRNA and protein levels in both HDLEC and MO‐LAS significantly, a phenomenon confirmed through immunofluorescence images. Additionally, Sm4 treatment suppressed the expression of key lymphatic phenotype markers (Prox1, Flt4, and Lyve1) and hindered migration in both HDLEC and MO‐LAS, all while maintaining cell viability. Conclusion These findings suggest that targeting SOX18 with Sm4 may hold potential as a therapeutic strategy for lymphangiosarcoma and cancer‐induced lymphatic metastasis. Further in vitro studies are warranted to investigate the mechanisms and conduct dose–response analyses to evaluate Sm4's potential as a targeted therapy for lymphangiosarcoma and cancer‐induced lymphangiogenesis in the future.